E-Tourism Communication: Hacking Business English Skills with Digital PBL (A Mixed-Methods Analysis) - Nadya Nurhidayah; Rusdiah Hasanuddin (Hasanuddin University, 2025)
This study employed a Convergent Parallel Mixed-Methods design to investigate the effectiveness of Digital Project-Based Learning (DPBL) in enhancing Business English Communication (BEC) outcomes for 15 E-Tourism students (N=15) following a 12-week intervention. Quantitative results showed high agreement on Authenticity (=4.60) and Digital Proficiency (=4.53), alongside significant perceived gains in oral (=4.13) and written (=3.93) communication skills. Qualitative data confirmed DPBL acted as a rapid